Longitudinal Analysis of Factors Associated with Successful Outcomes for Transition-Age Youths with Visual Impairments. (March 2014) - Connors, Elyse; Curtis, Amy; Emerson, Robert Wall; Dormitorio, Benedict
Introduction: Transition-age youths with visual impairments have higher rates of unemployment than their peers without impairment, and factors associated with success after graduation have been examined; however, it is unknown whether these factors remain influential across the first decade after exiting high school. Methods: Five waves of the 10-year National Longitudinal Transition Study–2 data were used for this analysis. The following factors—number of years since leaving high school, specific year exiting high school, paid work experience during high school, and high school completion— were examined for their longitudinal relationship with successful outcomes using generalized estimating equations. Results: Specific year exiting high school, paid work experience during high school, and high school completion were shown to be predictive of successful outcomes (as measured by post–high school employment or enrollment in post-secondary school or both). Youths with visual impairments who left high school in 2000–2002 were 2.2 times more likely to be successful when compared to those who left in 2006–2008 ( p < 0.05). Youths who worked for pay during high school were 3.6 times more likely to be successful compared to those who did not work for pay ( p < 0.01), while those who completed high school were 3.3 times more likely to be successful when compared to those who aged out or dropped out of high school ( p < 0.001). The amount of time spent away from high school was not significantly associated with post–high school success. Discussion: Completion of high school and paid work experience during high school are critical to long-term success for up to eight years post–high school. Taking into account specific years can be important in longitudinal studies. In this research, the recession appears to have significantly lowered success across all post–high school groups. Implications for practitioners: Professionals and families should encourage and support students with visual impairments to complete high school and to seek paid employment opportunities during high school.